Efektivitas Senam Hipertensi Untuk Pengendalian Tekanan Darah Bagi Penderita Hipertensi Di Prolanis Desa Karangasem - Dwi Rosella Komalasari; Konara Budi Sudrajat; Tessya Hadika Novitasari; Yngvie Salma Kirani; Aulia Safa’ Nabila; Wahyu Tri Sudaryanto (STIKes Ibnu Sina Ajibarang, 2023)
This significant increase in maximum temporal arterial blood pressure is referred to as hypertension. An average systolic blood pressure greater than 140 mmHg, or a systolic blood pressure greater than 90 mmHg, is referred to as hypertension. can also be further understood as an anomaly in capillary circulation pressure. Based on the type of high blood pressure, its causes can be divided into two categories: primary hypertension and secondary hypertension. The purpose of this study was to determine the impact of gymnastics (prolanis gymnastics) on heart health fluctuations in gymnastics participants in the Karangasem elderly gymnastics environment. The methodology used in this study was quasi-experimental analytic. The current study used original data collected from a sample of 17 people. April to June 2023 is the completion time of this study. Based on the mathematical analysis shown in Table 2, there was a considerable difference between systemic blood pressure and heart rate (p < 0.05), indicating that prolanis exercise had an impact on systolic blood pressure. However, there was actually no significant change (p>0.05) in systolic blood pressure. Based on analytical analysis, there were significant changes in systolic blood pressure and pulse rate (p < 0.05), indicating that prolanis exercise had an impact on systemic blood pressure. However, there was actually no significant change in blood pressure (p>0.05) in diastolic blood pressure. The Prolanis programme had an impact on systolic blood pressure, but no changes were seen in respondents in Karangasem Village in diastolic blood pressure measurements